Analisa Spasial Persebaran Fasilitas Publik di Kota Gorontalo Berbasis SIG - Farid F (Program Vokasi Universitas Negeri Gorontalo, 2026)
The spatial distribution of public facilities in Gorontalo City which experiences 1.67% annual population growth but faces uneven distribution of health, education, and trade facilities. The study aims to identify priority development areas using Geographic Information Systems with buffer zone analysis and facility gap index. Methods include collecting secondary data from BPS and related agencies, spatial processing using ArcGIS 10.8, and developing webGIS based on Leaflet.js and PHP MySQL. Results show 42% of the area is outside optimal reach of health facilities with South City and North City sub-districts having the highest gap indices (0.78 and 0.71), and 12 villages identified as priority areas. The developed webGIS system enables interactive visualization and spatial queries to support planning decision-making. The conclusion confirms that the GIS approach effectively identifies imbalances and serves as a strategic tool for local governments in planning equitable infrastructure.